Fiscal Policies to Address Climate Change in Asia and the Pacific - Dabla-Norris, Era (Departmental Papers; Departmental Paper ;, 2021)
Climate change is one of the greatest challenges facing policymakers worldwide, and the stakes are particularly high for Asia and the Pacific. This paper analyzes how fiscal policy can address challenges from climate change in Asia and the Pacific. It aims to answer how policymakers can best promote mitigation, adaptation, and the transition to a low-carbon economy, emphasizing the economic and social implications of reforms, potential policy trade-offs, and country circumstances. The recommendations are grounded in quantitative analysis using country-specific estimates, and granular household, industry, and firm-level data.